Chilling injury alleviation and quality maintenance of lemon basil by preharvest salicylic acid treatment - Suriyan Supapvanich; Rachadakorn Polpakdee; Pratumtip Wongsuwan (My University, 2015)
The purpose of this study was to alleviate chilling injury (CI) of lemon basil during storage by using preharvest salicylic acid (SA) treatment. The basil was sprayed with SA at the concentration of 0, 1, 5 or 10 mM before harvesting 24 h and was then stored at 7 °C for 4 days. Weight loss, CI score, malondialdehyde (MDA) content, electrolyte leakage (EL), superficial colour, pigments and bioactive compounds were determined. SA treatments alleviated CI and reduced the increase in EL and MDA content which the best result alleviating CI was 5 mM SA. The greenness and total chlorophyll content were maintained by SA application. After 24 h of treatment, antioxidants, total phenols and flavonoids were enhanced. During storage, SA treatment reduced the loss of bioactive compounds in the lemon basil. In conclusion, preharvest SA treatment at 5 mM alleviated CI and maintained quality of lemon basil during cold storage.
Keywords: Preharvest; Malondialdehyde; Postharvest Quality and Shelf Life Management